Visual-Based Information Technology as a Predictor of Islamic Religious Education Learning in the Merdeka Curriculum - Wulandari Wulandari; Mujiburrohman Mujiburrohman (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
Digital technologies are increasingly used to support student-centered instruction under Indonesia's Merdeka Curriculum, yet quantitative evidence from Islamic Religious Education (IRE) remains limited. This study examined the association between visual-based information technology and IRE learning. A cross-sectional explanatory survey involved 40 participants (33 students and 7 IRE teachers) purposively selected from one public junior secondary school. Two eight-item questionnaires used a four-point Likert scale, and internal consistency was acceptable for visual-based information technology (Cronbach's ? = 0.799) and IRE learning (? = 0.778). Data were analyzed using descriptive statistics, assumption tests, a two-tailed Pearson correlation with 5,000-sample bias-corrected and accelerated bootstrapping, and simple linear regression. Mean scores were 23.80 (SD = 5.85) for visual-based information technology and 24.15 (SD = 5.66) for IRE learning. Regression residuals were normally distributed (W = 0.959, p = 0.150), and no significant deviation from linearity was detected, F(16, 22) = 1.545, p = 0.170. A strong positive correlation was found, r = 0.861, p < 0.001, BCa 95% CI [0.764, 0.929]. Visual-based information technology significantly predicted IRE learning, B = 0.833, SE = 0.080, ? = 0.861, t = 10.454, p < 0.001, explaining 74.2% of the variance (R² = 0.742). The findings indicate a substantial association, but causal interpretation is limited by the single-school, cross-sectional, self-report design.